Femoral morphology asymmetry in hip dysplasia makes radiological leg length measurement inaccurate. (March 2019) - Tamura, K.; Takao, M.; Hamada, H.; Ando, W.; Sakai, T.; Sugano, N.
Abstract : Aims: The aim of this study was to examine whether hips with unilateral osteoarthritis (OA) secondary to developmental dysplasia of the hip (DDH) have significant asymmetry in femoral length, and to determine potential related factors. Patients and Methods: We enrolled 90 patients (82 female, eight male) with DDH showing unilateral OA changes, and 43 healthy volunteers (26 female, 17 male) as controls. The mean age was 61.8 years (39 to 93) for the DDH groups, and 71.2 years (57 to 84) for the control group. Using a CT-based coordinate measurement system, we evaluated the following vertical distances: top of the greater trochanter to the knee centre (femoral length GT), most medial prominence of the lesser trochanter to the knee centre (femoral length LT), and top of the greater trochanter to the medial prominence of the lesser trochanter (intertrochanteric distance), along with assessments of femoral neck anteversion and neck shaft angle. Results: The percentages of hips with an absolute difference of > 5 mm in femoral GT and LT lengths were significantly larger in the DDH group (24% for both) compared with those of the control group (2% and 7%, respectively). The femoral length GT of the affected femur was significantly shorter in Crowe I and longer in Crowe IV than that of the unaffected side. The affected-to-unaffected difference of the intertrochanteric distance showed positive correlation with that of the femoral length GT in Crowe I and Crowe II/III, and negative correlation with that of the femoral length LT in the Crowe I and Crowe IV groups. Conclusion: Hips with unilateral end-stage OA secondary to DDH show significant asymmetry in femoral length between both the greater and lesser trochanter and the knee compared with controls. The intertrochanteric distance was a morphological factor related to femoral-length asymmetry. When undertaking total hip arthroplasty (THA) in the presence of DDH, long leg radiographs or CT measurements should be used to assess true leg-length discrepancy. Cite this article: Bone Joint J 2019;101-B:297–302.